Protective effect of microbisporicin (NAI-107) against vancomycin resistant Enterococcus faecium infection in a Galleria mellonella model - Nele Hofkens; Zina Gestels; Saïd Abdellati; Philippe Gabant; Hector Rodriguez-Villalobos; Anandi Martin; Chris Kenyon; Sheeba Santhini Manoharan-Basil (Scientific Reports, 2024)
Abstract Increasing antimicrobial resistance in Enterococcus faecium necessitates the search for novel treatment agents, such as bacteriocins. In this study, we conducted an in vivo assessment of five bacteriocins, namely Lacticin Z, Lacticin Q, Garvicin KS (ABC), Aureocin A53 and Microbisporicin (NAI-107), against vanB-resistant Enterococcus faecium using a Galleria mellonella model. Our in vitro experiments demonstrated the efficacy of all five bacteriocins against vanB-resistant E. faecium with only NAI-107 demonstrating in vivo efficacy. Notably, NAI-107 exhibited efficacy across a range of tested doses, with the highest efficacy observed at a concentration of 16 µg/mL. Mortality rates in the group treated with 16 µg/mL NAI-107 were lower than those observed in the linezolid-treated group. These findings strongly suggest that NAI-107 holds promise as a potential alternative therapeutic agent for treating infections caused by resistant E. faecium and warrants further investigation.